Myocardial tissue characterization by contrast-enhanced cardiac magnetic resonance imaging in subjects with prediabetes, diabetes, and normal controls with preserved ejection fraction from the general population - Storz, Corinna; Schlett, Christopher L. (European heart journal - cardiovascular imaging, 2018)
AbstractAims. To characterize changes in the myocardium in subjects with prediabetes, diabetes, and healthy controls with preserved left ventricular ejection f